Pentingnya Mediasi Dalam Mengurangi Kasus Perceraian DiPengadilan Agama Banyumas - Teguh Anindito; Aris Priyadi; Arif Awaludin (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2022)
Mediation as one of the tools that is needed in dealing with divorce cases is very important. Many divorcecases are resolved through mediation. Research conducted at the Banyumas Religious Court usingnormative juridical methods shows that mediation still needs to be socialized to resolve the various divorcecases that have piled up at the Banyumas Religious Court. It is necessary to overcome various obstacles inresolving cases through this mediation. Minimizing obstacles will help achieve optimal mediation. Effortsmade by the Supreme Court by making Supreme Court Regulations further strengthen the role of mediationin settling cases.